Proliferative Responses of Rabbit Lymphocytes to Pasteurella multocida Decrease with Prolonged Immunization - Skaletsky, Eileen (1982)
Peripheral blood and splenic lymphocytes from rabbits immunized with Pasteurella multocida by various schedules were stimulated to undergo blast transformation in vitro in response to this antigen. Repeated immunizations suppressed this response.